Praktik Akad Jual Beli Lembu - Harahap, Abdul Manaf (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
There was bartering of oxen for land, because the disaster expert did not have cash to pay for the ox, he only had a plot of land which in comparison to the price of the ox was not worth the price. In the initial agreement, the ox was paid with a piece of land, and in the agreement there was no authentic evidence to prove that the agreement was that the ox was paid with a piece of land owned by the disaster expert. The problem in this thesis is how the implementation of the bull sale and purchase contract and how the Fiqh Muamalah view of the bull sale and purchase contract with a plot of land in the VII Neighborhood of Gunung Tua Market, Padang Bolak District, North Padang Lawas Regency. The purpose of this study was to determine the implementation of the bull sale and purchase contract and to know the view of muamalah fiqh on the implementation of the bull sale and purchase contract with a plot of land in the VII Neighborhood of Gunung Tua Market, Padang Bolak District, Padang Lawas Utara Regency. This type of research is field research using qualitative descriptive analysis method. The approach of this research is by means of observation, interviews, and documentation based on the provisions of Islamic law and customary law in force and related to the implementation of the bull sale and purchase contract in the VII Neighborhood of Gunung Tua Market, Padang Bolak District, Padang Lawas Utara Regency. The informants interviewed were environmental leaders VII, religious leaders, bull buyers and ox sellers. The results of this research are bull sellers and buyers of oxen in the VII neighborhood of Gunung Tua Market know that what they are doing is wrong, but they close their eyes to what is happening because it has become a habit, then with urgent things without being noticed that suddenly come. without any preparation to make ox buyers do this. bull sellers who are mature and competent in legal action as well as cattle buyers who are mature and able to distinguish between good and bad. the object of sale and purchase, namely the goods being traded must be known (seen), clearly, their quantity, weight, and other measurements.